2012
DOI: 10.1111/j.1460-2466.2012.01682.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring How We Enjoy Antihero Narratives

Abstract: Affective disposition theory (ADT), which nicely explains enjoyment of traditional hero narratives, appears somewhat limited in its ability to explain antihero narratives, primarily because of the moral complexity of the protagonists. Recent work proposes that viewers over time develop story schema that permit antihero enjoyment, despite character immorality. This article reports results from three studies that support this claim. Specifically, the findings indicate that moral judgment may be less important to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
88
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 19 publications
2
88
0
6
Order By: Relevance
“…Several studies have shown anti-heroes are positively related to media enjoyment (Janicke & Raney, 2015;Shafer & Raney, 2012;Tsay & Krakowiak, 2011). Part of the issue may lie in the reliance on ADT to understand positive valuation of characters and subsequent emotional response.…”
Section: Character Morality and Enjoymentmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have shown anti-heroes are positively related to media enjoyment (Janicke & Raney, 2015;Shafer & Raney, 2012;Tsay & Krakowiak, 2011). Part of the issue may lie in the reliance on ADT to understand positive valuation of characters and subsequent emotional response.…”
Section: Character Morality and Enjoymentmentioning
confidence: 99%
“…A recent study suggests that even though MACs have been part of the television landscape for a long time, over the last years there has been a significant increase in their presence in the television landscape (Daalmans, Hijmans, & Wester, 2013). Therefore, scholars have started to more systematically study characters with less clear-cut morality (e.g., Eden et al, 2011;Janicke & Raney, 2015;Krakowiak & Tsay-Vogel, 2013Shafer & Raney, 2012;Tamborini, Weber, Eden, Bowman, & Grizzard, 2010). Eden et al (2011) and Tamborini et al (2010) found that over the course of viewing narrative media, distinct hero, villain, and ambiguously moral characters emerge from ensemble casts, and can be identified by a) how well they uphold or violate moral norms, and b) how well they are rewarded or punished by the narrative, in line with ADT.…”
Section: Morality Predicts Enjoyment 351mentioning
confidence: 99%
See 2 more Smart Citations
“…The success of the hero myth can be explained by ADT [20]. ADT creates expectations about characters or, for present purposes, athletes.…”
Section: Affective Disposition Theorymentioning
confidence: 99%